2023
DOI: 10.1038/s41598-023-34118-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of aortic valve calcium scoring in various etiologies of aortic stenosis

Wisarut Wanchaitanawong,
Rungsrit Kanjanavanit,
Tanop Srisuwan
et al.

Abstract: Most of the studies about aortic valve calcium (AVC) score in aortic stenosis (AS) were based on degenerative or bicuspid AS but not rheumatic AS. We aimed to study the diagnostic accuracy of AVC score to determine severe AS in various etiologies. Adult patients diagnosed with mild to severe AS were enrolled. AVC score were identified from multi-detector computed tomography (MDCT) scan. The AVC score was highest in bicuspid AS (3211.9 (IQR (1100.0–4562.4) AU) compared to degenerative AS (1803.7 (IQR (1073.6–25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Interestingly, this is much lower than the previously identified cut-offs for TAV patients [77], despite paradoxically reporting a higher mean AVCS in BAV with severe AS at 3497.71 ± 2470.17 AU. Contrasting with this study, Wanchaitanawong et al identified an AVCS cut-off in BAV patients (n = 43) to be much higher than that noted by Ren et al, with cut-offs closer to those with severe AS with three cusps; AVCS ≥ 1145 AU (sensitivity 83.3%, specificity 80%) for females and ≥2431.8 AU (sensitivity 92.9%, specificity 71.4%) for males [78].…”
Section: Avcs and Bavcontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, this is much lower than the previously identified cut-offs for TAV patients [77], despite paradoxically reporting a higher mean AVCS in BAV with severe AS at 3497.71 ± 2470.17 AU. Contrasting with this study, Wanchaitanawong et al identified an AVCS cut-off in BAV patients (n = 43) to be much higher than that noted by Ren et al, with cut-offs closer to those with severe AS with three cusps; AVCS ≥ 1145 AU (sensitivity 83.3%, specificity 80%) for females and ≥2431.8 AU (sensitivity 92.9%, specificity 71.4%) for males [78].…”
Section: Avcs and Bavcontrasting
confidence: 99%
“…This was postulated to be a result of the pattern of calcium distribution, with a higher calcium load found on the aortic commissure compared to the valve leaflets (as is seen in TAV and BAV AS). These patients were also younger than typical TAV or BAV patients with AS, noting that age is a significant risk factor for the incidence of AV calcification [78].…”
Section: Potential Limitations Of Avcsmentioning
confidence: 83%
See 2 more Smart Citations